Optimised synthesis of a nitroCBI hypoxia-activated prodrug with substantial anticancer activity. Issue 22 (31st May 2019) - Lee, Ho H.; Dickson, Benjamin D.; Stevenson, Ralph J.; Yang, Shangjin; Tercel, Moana
Abstract: An optimised synthesis of a hypoxia-activated anticancer prodrug related to the duocarmycin family of natural products is described. The improved 10-step synthesis increases the overall yield from 4.4% to over 40% while requiring just 2 chromatography-based purifications. The most significant improvements optimise the isomer distribution in a key chlorosulfonylation reaction, and facilitate the removal of tin residues from a tributyltin hydride-mediated radical reaction. Improved preparations of two side chains are also reported. The new method provides practical access to sufficient material to support advanced efficacy and toxicology assessments. Graphical abstract: Image 1